SMK Pesantren: Sebuah Penelusuran Akar Ideologi Pendidikan - AÃ¢Â€Â™isyah, Siti (DirÄsÄt: Jurnal Manajemen dan Pendidikan Islam, 2017)
This article discusses about SMK Pesantren with a focus on the search of itâs educational ideology. As the perspective, this article uses the theory of educational ideology from Giroux and Aronowitz (conservative, liberal and critical), as well as Freireâs consciousness theory (magical, naive, and critical). Based on the background that SMK and pesantren, epistemologically, depart from different, and even contradictive, ideological ideals. Being seen from the ideological theory initiated by Giorux and Aronowitz, pesantren education can be included into conservative and critical categories, while vocational education is more appropriate to be included in the liberal category. As seen from the Freire consciousness theory, pesantren education can uniquely combine magical and critical awareness, while vocational education departs from naive consciousness. Could educational institutions depart from the critical ideology as well as the liberals simultaneously? Could a naive consciousness be coupled with a critical awareness of the same entity? This article tries to answer these questions with the main purpose of SMK Pesantren is not mutually disagree between the two entities that build it, namely SMK and pesantren.